2018
DOI: 10.1159/000493236
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 Inhibits Proliferation and Metastasis of Hypertrophic Scar Fibroblasts via Targeting Pleiotrophin

Abstract: Background/Aims: There are few effective treatment options for hypertrophic scars. MircoRNAs are a class of small, noncoding RNAs involved in multiple biological functions. Methods: Gene chip screening was used to screen out the differential expression of miRNAs in hypertrophic scars and normal tissues. Western blot and real-time PCR were used to confirm the expression of pleiotrophin (PTN) in hypertrophic scars. After analyze the correlation between PTN and miR-137 using correlation analysis, we used miRDB so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…These exuberant responses start the formation of collagen and even keloids . The innovative and targeted therapeutics have recently drawn our attention by medicating the expression of miRs for curing these diseases . In the current study, we found that BAI effectively eliminated the proliferation of fibroblast cells and TGF‐β1‐induced synthesis of collagen.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These exuberant responses start the formation of collagen and even keloids . The innovative and targeted therapeutics have recently drawn our attention by medicating the expression of miRs for curing these diseases . In the current study, we found that BAI effectively eliminated the proliferation of fibroblast cells and TGF‐β1‐induced synthesis of collagen.…”
Section: Discussionmentioning
confidence: 53%
“…17 The innovative and targeted therapeutics have recently drawn our attention by medicating the expression of miRs for curing these diseases. [18][19][20] In the current study, we found Fibroblast NIH-3T3 cells were pretreated with BAI (150 μM) for 12 hours after transfection of miR-29 inhibitor and its consistent NC. Fibroblast NIH-3T3 cells did not accept the transfection of miR-29 inhibitor or pretreatment of BAI in the CTRL.…”
Section: Discussionmentioning
confidence: 62%
“…in addition, an abundance of evidence has identified that mirnas were involved in numerous metabolic reactions, including cell proliferation, differentiation, autophagy and apoptosis, by directly binding to the 3'-untranslated region (3'-uTr) of their target mrnas (23)(24)(25)(26). To date, a small number of studies have suggested a potential role between mirnas and HSs; for example, the expression levels of mir-21 were reported to be upregulated in HS-derived fibroblasts (HSFBs) and inhibiting miR-21 expression significantly slowed the formation of HSs in vivo (27). Conversely, the expression levels of another miRNA, miR-137, were markedly downregulated in HSs, which induced the proliferation and metastasis of fibroblasts (28).…”
Section: Resveratrol Inhibits Hypertrophic Scars Formation Bymentioning
confidence: 99%
“…By mediating post-transcriptional regulation, they exert various biological functions, including proliferation, apoptosis, and invasion (2). For instance, Zhang et al reported that the downregulation of miR-137 expression can induce the proliferation and metastasis of skin fibroblasts, and promote HS formation and development (3). Furthermore, a study by Wu et al showed that miR-155 was downregulated in both HS tissues and HS-derived fibroblasts, and therefore suggested it as a potential therapeutic target for HS (4).…”
Section: Introductionmentioning
confidence: 99%